PENGARUH MULTINASIONALITAS DAN THIN CAPITALIZATION TERHADAP TAX AVOIDANCE DENGAN TAX HAVEN SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2016-2021 (Data Empiris Pada Industri Manufaktur yang Terdaftar - Jamilah, Nurul; Ginajar, Seandy (JURNAL RISET AKUNTANSI TIRTAYASA, 2024)
This study aims to determine the effect of multinationality and thin capitalization on tax avoidance with tax havens as a moderating variable. The research sample used in this research is all manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2021 period. This research is a type of quantitative research. Data analysis was performed using multiple linear regression models and moderated regression analysis (MRA). In selecting the sample, this study used a purposive sampling method. This study uses secondary data based on financial statements of manufacturing companies obtained from the Indonesian Stock Exchange website. Data processing was carried out using the SPSS 25 application program. The results showed that the multinationality variable had no effect on tax avoidance. Meanwhile, the thin capitalization variable has a positive effect on tax avoidance. Meanwhile, the results of the moderated regression analysis (MRA) show that the tax haven variable cannot moderate the effect of multinationality and thin capitalization on tax avoidance.